Pengaruh Penerapan Model Pembelajaran Contextual Teaching and Learning terhadap Kemampuan Komunikasi Matematis berdasarkan Self Confidence Siswa SMP/MTs - Siti Rahmi; H Hasanuddin (Instructional Development Journal, 2019)
Abstract: This study aims to determine the effect of 'Contextual Teaching and Learning' on students 'mathematical communication skills in terms of students' self-confidence. This research uses factorial design. The population in this study were all students of class VII Madrasah Tsanawiyah Ansharullah Birandang Island in the academic year 2018/2019. The sample of this study is students of class VII.B as an experimental class and class VIII as a control class. The instrument used was a questionnaire instrument to measure the level of students 'Self Confidence and description tests to measure students' mathematical communication skills. Data were analyzed using two-way ANOVA. Based on the results of data analysis, it can be concluded that: 1) There are differences in mathematical communication skills between students who take the CTL learning model and students who take conventional learning. 2) There is no influence of the interaction between CTL learning models with Self Confidence on students' mathematical communication skills. Thus in general the CTL learning model influences students' mathematical communication skills.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh 'Contextual Teaching and Learning' terhadap kemampuan komunikasi matematis siswa ditinjau dari self-confidence siswa. Penelitian ini menggunakan disain faktorial. Populasi dalam penelitian ini adalah seluruh siswa kelas VII Madrasah Tsanawiyah Ansharullah Pulau Birandang tahun ajaran 2018/2019. Sampel penelitian ini adalah siswa kelas VII.B sebagai kelas eksperimen dan kelasVII.A sebagai kelas kontrol. Instrumen yang digunakan adalah instrumen angket tuntuk mengukur tingkat Self Confidence siswa dan tes uraian untuk mengukur kemampuan komunikasi matematis siswa. Data dianalisis dengan menggunakan anova dua arah. Berdasarkan hasil analisis data dapat diambil kesimpulan bahwa: 1) Terdapat perbedaan kemampuan komunikasi matematis antara siswa yang mengikuti model pembelajaran CTL dengan siswa yang mengikuti pembelajaran konvensional. 2) Tidak terdapa tpengaruh interaksi antara model pembelajaran CTL dengan Self Confidence terhadap kemampuan komunikasi matematis siswa. Dengan demikian secara umum model pembelajaran CTL berpengaruh terhadap kemampuan komunikasi matematis siswa.